ESTIMATION OF ARSENIC AND MERCURY IN FISHES FROM RIVER GANGA FOR RIVERINE ECOSYSTEM HEALTH BIOMONITORING AND ASSESSMENT - MOHANTY, BIMAL PRASANNA; GANGULY, SATABDI; MAHANTY, ARABINDA; MITRA, TANDRIMA; PARIA, PRASENJIT; BEHERA, BIJAY KUMAR; DAS, BASANTA KUMAR (Journal of the Inland Fisheries Society of India, 2021)
Concentration of pollutants in fish tissues is a true reflection of their concentration in the ecosystem. In this context, toxic environmental contaminants arsenic and mercury in fishes from river Ganga were investigated by inductively-coupled plasma mass spectrometry (ICP-MS) to assess the level of these contaminants in different stretches of the river. Total arsenic concentrations in Tenualosa ilisha, Sperata seenghala, Amblypharyngodon mola and Puntius sophore were 0.02-2.9 mg kg-1 which is within the permissible limit for human consumption. Mean mercury content was below the permissible level (0.003-0.05 mg kg-1) in all fishes analyzed from different stretches. This biomonitoring study showed that river Ganga, in the indicated and adjoining stretches, appears to be free from arsenic and mercury contamination. This study demonstrated the dual benefits associated with using fish as biomonitors; it serves as a tool for riverine ecosystem health monitoring and also provides information on food safety.Key words: Arsenic, ICP-MS, Fish biomonitors, Food safety, Mercury, Riverine ecosystem health biomonitoring